Cost-utility analysis of the inhaled steroids available in a developing country for the management of pediatric patients with persistent asthma (2013)
Introduction. The choice among the different treatments available can have a great impact on the costs of asthma, Objectives. The objective of this study was to estimate the incremental cost-utility ratio of three inhaled corticosteroids (ICs): budesonide (BUD), fluticasone propionate (FP), and ciclesonide, compared to beclomethasone dipropionate (BDP) (the only IC included in the Compulsory Health Insurance Plan of Colombia), Methods. A Markov-type model was developed to estimate costs and health outcomes of a simulated cohort of patients less than 18 years of age with persistent asthma treated over a 12-month period. Effectiveness parameters were obtained from a systematic review of the literature. Cost data were obtained from a hospital´s bills and from the national manual of drug prices. The study assumed the perspective of the national healthcare in Colombia. The main outcome was the variable “quality-adjusted life years” (QALY), Results. While treatment with BDP was associated with the lowest cost (£106.16 average cost per patient during 12 months), treatment with FP resulted in the greatest gain in QUALYs (0.9325 QALYs). FP was associated with a greater gain in QALYs compared to BUD and ciclesonide (0.9325 vs. 0.8999 and 0.9051 QALYs, respectively) at lower costs (£231.19 vs. £309.27 and £270.15, respectively), thus leading to dominance. The incremental cost-utility ratio of FP compared to BDP was £19,835.28 per QALY, Conclusions. BDP is the most cost-effective therapy for treating pediatric patients with persistent asthma when willingness to pay (WTP) is less than £21,129.22/QALY, otherwise, FP is the most cost-effective therapy.